YIELD OF SPUTUM INDUCTION FOR THE DETECTION OF MYCOBACTERIUM TB IN SPUTUM SCARCE PRESUMED PULMONARY TUBERCULOSIS CASES - Sohail Khan Raja; Zulqarnain Mustafa Mughal; Kainat Rashid; Muhammad Moeed Iqbal; Saad Bin Mushtaq; Maryam Arif; Arsalan Bin Zafar; Zainab Shahab; Syeda Sana Fatima; Muhammad Ali Shahid; Samina Anjum (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Tuberculosis (TB) is an infectious disease caused by bacteria called mycobacterium TB. It mainly targets the lungs, although in some severe cases, this infection can be transferred from an infected individual to other organs in the body. TB remains one of the major global health threats, particularly for countries like Pakistan, where it does fall amongst the causes of the top ten mortalities.Objectives: The main objective of the research was to assess the yield of TB positive in induced sputum with hypertonic saline among patients presenting with sputum scarcity.Methodology: This cross-sectional study was carried out at the Abbas Institute of Medical Sciences Hospital, Muzaffarabad, AJK. In total, 54 patients were subjected to sputum induction.Results: Subsequent tests confirmed that 55.6% of the subjects were tested positive for mycobacterium TB using Genexpert. Radiological evidence and family history of TB were also analyzed among MTB positive and negative cases.Conclusion: The obtained results from this study provide evidence that sputum induction could be a useful diagnostic tool, especially in patients with scarce sputum, and further that it offers characteristics giving insights into the distribution of TB-related features of the studied cohort.